2012
DOI: 10.1136/bmjqs-2011-000007
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported violations during medication administration in two paediatric hospitals

Abstract: Content Violations of safety protocols are paths to adverse outcomes that have been poorly addressed by existing safety efforts. This study reports on nurses' self-reported violations in the medication administration process. Objective To assess the extent of violations in the medication administration process among nurses. Design, Setting, & Participants Participants were 199 nurses from two U.S. urban, academic, tertiary care, free-standing pediatric hospitals who worked in: a pediatric intensive care un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 26 publications
0
31
0
1
Order By: Relevance
“…For example, studies in anesthesiology (Beatty & Beatty, 2004; de Saint Maurice, Auroy, Vincent, & Amalberti, 2010; Phipps et al, 2008) reveal reasons for safety violations related to the violated rule, the worker, including worker perceptions (Phipps, Parker, Meakin, & Beatty, 2010), and various organizational factors including time pressure, goal conflict, resources and equipment design. These studies, as well as studies in surgery (R. McDonald, Waring, & Harrison, 2006), intensive care nursing (Drews, Wallace, Benuzillo, Markewitz, & Samore, 2012), and pediatric nursing (Alper et al, 2012) also demonstrate that various factors interact to promote violations. For example, a survey of 199 nurses in two pediatric hospitals showed that medication administration process violations depended on a combination of the situation (routine vs. emergency), setting (medical/surgical vs. oncology unit) and task (checking patient identification vs. documenting administration) (Alper et al, 2012).…”
Section: Focused Reviews On Macroergonomics Topics In Healthcare Qmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, studies in anesthesiology (Beatty & Beatty, 2004; de Saint Maurice, Auroy, Vincent, & Amalberti, 2010; Phipps et al, 2008) reveal reasons for safety violations related to the violated rule, the worker, including worker perceptions (Phipps, Parker, Meakin, & Beatty, 2010), and various organizational factors including time pressure, goal conflict, resources and equipment design. These studies, as well as studies in surgery (R. McDonald, Waring, & Harrison, 2006), intensive care nursing (Drews, Wallace, Benuzillo, Markewitz, & Samore, 2012), and pediatric nursing (Alper et al, 2012) also demonstrate that various factors interact to promote violations. For example, a survey of 199 nurses in two pediatric hospitals showed that medication administration process violations depended on a combination of the situation (routine vs. emergency), setting (medical/surgical vs. oncology unit) and task (checking patient identification vs. documenting administration) (Alper et al, 2012).…”
Section: Focused Reviews On Macroergonomics Topics In Healthcare Qmentioning
confidence: 91%
“…Far less attention has been paid to the occurrence and causes of intentional safety violations that affect patient safety largely independent of unintended errors (Amalberti, Vincent, Auroy, & de Saint Maurice, 2006). In the context of patient safety, safety violations (or workarounds) have been defined as deliberate acts that deviate from “rules and standards” (Amalberti, Vincent, Auroy, & de Saint Maurice, 2006, p. i66) or “established protocols of practice” (Phipps et al, 2008, p. 1626), or acts that break “rules, policies, protocols or procedures” (Alper et al, 2012, p. 408). Some note that safety “rules” in health care are incredibly varied, ranging from broad or contested guidelines, to exact and widespread procedures, to institution-specific policies and informal norms, to diagnostic or therapeutic “orders” (Amalberti, Vincent, Auroy, & de Saint Maurice, 2006; de Saint Maurice, Auroy, Vincent, & Amalberti, 2010; Phipps et al, 2008).…”
Section: Focused Reviews On Macroergonomics Topics In Healthcare Qmentioning
confidence: 99%
“…In this sense, several publications presented satisfactory results in patient safety resulting from redesign of work processes and involvement of healthcare professionals. (11,12) It was observed that medication-related incidents were common in intensive care units. And although a very small fraction caused harm to patients, it is still necessary to manage the risks related to the medication process, considering that critical patients present higher needs for care and are therefore more vulnerable.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of violations across a range of industries (including, but not limited to, healthcare) suggests worker-centred design, training, competing goals and rule definition, as predictors as well as individual characteristics 42. For example, in medication administration, violations may be influenced by context, process and hospital location 43. Anaesthesiologists’ decisions to follow or deviate from guidelines are influenced by the beliefs they hold about the consequences of their actions, the direct or indirect influence of others, and the presence of factors that encourage or facilitate particular courses of action 44.…”
Section: Systems Models Of Compliancementioning
confidence: 99%